2021
DOI: 10.1038/s41598-021-87032-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous auricular vagus nerve stimulation induces stabilizing modifications in large-scale functional brain networks: towards understanding the effects of taVNS in subjects with epilepsy

Abstract: Transcutaneous auricular vagus nerve stimulation (taVNS) is a novel non-invasive brain stimulation technique considered as a potential supplementary treatment option for subjects with refractory epilepsy. Its exact mechanism of action is not yet fully understood. We developed an examination schedule to probe for immediate taVNS-induced modifications of large-scale epileptic brain networks and accompanying changes of cognition and behaviour. In this prospective trial, we applied short-term (1 h) taVNS to 14 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
23
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 53 publications
8
23
3
1
Order By: Relevance
“…After the end of the stimulation, this effect was enduring. This result contrasts findings from the study by von Wrede et al ( 2021 ), where the same enduring effect was observed, but the immediate effect of the stimulation perceived to be reverse (in median a decrease in integration and a increase in segregation). For stability- and robustness-associated network characteristics, we here observed almost no immediate change in assortativity, i.e., in the vulnerability to synchronize.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…After the end of the stimulation, this effect was enduring. This result contrasts findings from the study by von Wrede et al ( 2021 ), where the same enduring effect was observed, but the immediate effect of the stimulation perceived to be reverse (in median a decrease in integration and a increase in segregation). For stability- and robustness-associated network characteristics, we here observed almost no immediate change in assortativity, i.e., in the vulnerability to synchronize.…”
Section: Discussioncontrasting
confidence: 99%
“…In the previous study, the immediate stimulation-induced effect also indicated a decreased vulnerability to synchronize and a decreased stability of the synchronized state. The discrepancies between the current and the study by von Wrede et al ( 2021 ) are possibly the result of our larger group of subjects (30 vs. 14) and the inclusion of subjects with a broader range of different pathologies and etiologies, which also may assist in explaining the larger inter-subject variability of modifications of global network characteristics observed here. Further studies might shed light on the existence of different subgroups of subjects and the influence of such subgroups on taVNS-induced modifications of topological and stability- and robustness-associated network properties.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations